The Unofficial Guide Photoshop Elements 4 - L.Baker Donna (Wiley, 2006)
Photoshop Elements has the power to transform your digital images, but to use itwith confidence you'll need to know its quirks and shortcuts. Find out what the manual doesn't always tell you in this insider's guide to using Elements in the real world. Can you eliminate red eye and dark circles? Is there a way to simplify the output process? From discovering how to glamorize photos to creating high-impact slideshows for work or Web--first get the official way, then the best way from an expert.